SEPARATION OF COTTON FROM AIRFLOW IN PNEUMATIC TRANSPORT SYSTEMS OF THE COTTON INDUSTRY - Sharibaev, Nosir; Makhmudov, Azimjon (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
This research focuses on enhancing the efficiency of cotton separation from airflow in pneumatic transport systems within the cotton industry. The study investigates the aerodynamic properties of separators, material characteristics, and challenges faced in the separation process. By introducing advanced technologies and optimizing separator designs, it becomes possible to regulate airflow, separate cotton without causing damage, and minimize energy consumption. The findings demonstrate that these improvements can enhance factory productivity and elevate the quality of cotton fiber. The outcomes of this research hold potential for fostering sustainable development in the cotton industry.